Philosophical Problems With the Gender-Critical Feminist Argument Against Trans Inclusion. (May 2020) - Zanghellini, Aleardo
The Reform of the Gender Recognition Act: Government Consultation (2018) catalyzed a heated debate on transgender rights and trans inclusion in the United Kingdom. I start by explaining what the reforms to the U.K. system of gender recognition propose, why gender-critical feminists oppose them, and how other feminist academics have responded to their arguments. I then offer a more detailed philosophical critique of gender-critical trans-exclusionary feminist arguments. I argue that the gender-critical feminist case against trans women's access to women-only (or sex-segregated, or single-sex) spaces suffers from a number of fallacies, and introduces modes of argument that are at odds with well-established and sound uses of practical reason. I try to make sense of these problems with gender-critical feminist thought by appealing to the idea of presupposed paranoid structuralism. I also argue that gender-critical feminists' enthusiastic use of social media and allied online platforms may be implicated in generating some of these problems.